1997
DOI: 10.1177/030802269706000903
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Student Health Professionals: A Literature Review

Abstract: IS article discusses the mental health problems of students, based on a review of previous research studies. Although a university education Is regarded as a .privilege, studying for a degree can be a demanding and stressful experience. Many students experience episodes of psychological distress during their college years. Professional degree programmes (such as occupational therapy or medicine) are particularly stressful relative to some other courses, because students face both academic and clinical demands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…They are away from the supports that they would normally receive at home, and experience various difficulties such as language, finance and social alienation, and pressure to achieve satisfactory academic objectives within a limited period of time [17,18]. International students have been reported as experiencing a significantly higher level of "homesickness" than local students [19] and are more likely to be diagnosed with psychological distress or clinical depression [20,21]. Although many university students are not yet sexually active, it is possible that all of these factors might affect their later sexual risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…They are away from the supports that they would normally receive at home, and experience various difficulties such as language, finance and social alienation, and pressure to achieve satisfactory academic objectives within a limited period of time [17,18]. International students have been reported as experiencing a significantly higher level of "homesickness" than local students [19] and are more likely to be diagnosed with psychological distress or clinical depression [20,21]. Although many university students are not yet sexually active, it is possible that all of these factors might affect their later sexual risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, recommendations for psychologic counseling services for medical students have been made by many. 7,8 The British Medical Association 9 has strongly suggested that medical schools that have not already adopted strategies that recognize the importance of psychologic services review their educational objectives. Whereas most veterinary colleges report recognizing the importance of psychologic services, a far lower percentage have implemented services directed specifically toward veterinary students.…”
Section: Discussionmentioning
confidence: 99%
“…Professional degree programmes are acknowledged as stressful due to the combination of academic and clinical demands (Tyrrell 1997); however, effective coping strategies can mitigate the impact of stress during academic studies and may also benefit the student post qualification (Everly et al 1994). Few studies address stress in undergraduate occupational therapy programmes, therefore this research investigated occupational therapy students' experience of stress, stressors and coping strategies during campus-based training.…”
Section: Ethical Approvalmentioning
confidence: 99%